“Excluded phenotypes” restrict genetic paths toward adaptation in declining populations - James S. Andon; Charles D. Kocher; Ken A. Dill; Tina Wang (Proceedings of the National Academy of Sciences, 2026)
Evolutionary rescue is the process by which declining populations adapt to conditions that would otherwise cause their extinction. Considering the spectrum of mutant phenotypes that can arise within a declining population, there exists the interesting case of mutations which improve fitness relative to the wild-type, but do not restore population growth. Here, we hypothesize that mutations within this phenotype space are functionally inaccessible to populations in decline and term it an “evolutionary excluded zone.” We experimentally demonstrate that this excluded zone disallows certain mutational paths from causing evolutionary rescue in declining populations of M13 bacteriophage. We then integrate this observation into Fisher’s Geometric Model to extrapolate it to other evolutionary rescue scenarios. Our findings indicate that the excluded zone significantly reduces the likelihood of evolutionary rescue by de novo mutation and that evolution is fundamentally different in declining populations than in ones that are constant or growing.